Students' Neuro-Psychological Readiness In The Deep Learning Approach: An Exploratory Study - Raysha Zahra Harahap; Yohana Imelda Tampubolon; Chintya Angelina Sinambela; Trinita Ivana Rumapea; Reymond Dwi Putra Sinaga; Dika Kristina Lambok Manurung; Selviana Napitupulu (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This study aims to measure students' neuro-psychological readiness as a prerequisite for implementing deep learning, encompassing executive functions, metacognition, intrinsic motivation, and emotional regulation, through the dimensions of mindful, meaningful, and joyful learning. The research employed a mixed-methods approach with a sequential exploratory design dominated by quantitative data. The study was conducted at SMA Negeri 1 Pematangsiantar, involving a sample of 130 students from grades X and XI selected through stratified random sampling. Quantitative data were collected using a 5-point Likert-scale questionnaire grounded in Diamond's executive functions framework. The results indicate that students' neuro-psychological readiness falls within the moderate-to-high category, with an overall mean of 3.57. The mindful learning dimension recorded the highest score (mean 3.62), followed by joyful learning (3.55), and meaningful learning (3.48). Data distribution across all dimensions was confirmed as normal; however, 12–18 percent of students were in the low category, indicating vulnerability to distractions, difficulties in constructing meaningful understanding, and low emotional resilience when facing learning challenges. These findings suggest that although the majority of students possess an adequate foundation for deep learning, readiness gaps remain that could potentially hinder the effectiveness of curriculum implementation. Based on these results, the study recommends incorporating brief mindfulness exercises into teaching, strengthening integrated cross-subject projects accompanied by metacognitive strategies, and adopting learning approaches that foster intrinsic motivation and a growth mindset. Additionally, ongoing teacher training in educational neuropsychology, periodic assessment of student readiness, and school policies on device management are required.